Severe asthma: oral corticosteroid alternatives and the need for optimal referral pathways. (3rd April 2021) - Cataldo, Didier; Louis, Renaud; Michils, Alain; Peché, Rudi; Pilette, Charles; Schleich, Florence; Ninane, Vincent; Hanon, Shane
Abstract: Objective: Patients with severe asthma require high-dose inhaled corticosteroids, with or without add-on treatments, to maintain asthma control. Because symptom control remains unsatisfactory in some patients despite these therapies, maintenance therapy with oral corticosteroids (OCS) remains considered a treatment option by physicians. Besides physician-diagnosed exacerbations, many patients intermittently self-medicate with OCS during episodes of worsening symptoms or as a prevention of such episodes. However, long-term OCS use is associated with several comorbidities that may decrease health-related quality of life, worsen prognosis, and should ideally require monitoring and management. In this review, we discuss the adverse effects of OCS use, the OCS-sparing effect of biologics in severe asthma, and the need for optimal referral pathways to ensure the best outcomes for those at-risk asthma patients. Data sources: PubMed. Study selection: Studies with results on the OCS-sparing effect of biologics in adult severe asthma were selected. Results: Chronic and intermittent OCS use in asthma is associated with considerable adverse effects in asthma. Omalizumab, mepolizumab, benralizumab, and dupilumab reduce the need for OCS in severe asthma, while also reducing the exacerbation rate and improving several patient-related outcomes. Conclusion: Targeted biologic therapies have revolutionized the treatment of uncontrolled severe asthma by reducing or even eliminating the need for OCS and improving other major outcomes. Novel agents are now rapidly increasing the therapeutic armamentarium, but additional efforts are needed to optimize referral pathways in order to ensure sustainable access to these therapies.